Deductibility of actual expenditure and losses incurred, respectively, as a result of theft or defalcation and liability for damages or compensation - Ngalwana,Vuyani R (Department of Commercial Law, 2023)
The area of income tax law in South Africa pertaining to the deductibility of expenses and losses incurred, respectively, as a result of theft or defalcation, on the one hand, and liability for damages or compensation, on the other, is replete with uncertainty particularly in light of the courts' inconsistency on this subject. Indeed, on review of case law in this area it appears, with respect, that in some cases the judicial personages, rather than have regard to the applicable principles, are prone to 'cut the sails to fit the trim' once a decision has been made to rule the one way or the other. The courts' inconsistencies and the resultant uncertainty on the part of taxpayers are, in my view, also exarcebated where more than one approach -- often leading to contrasting results -- to resolving the problem at hand are apposite. On such occasions it is difficult to fault the court's tendency to decide a case · consistently with its unarticulated policy considerations. Finally, another factor that, in my view, contributes to the uncertainty and inconsistency in this area of income tax law is the old judicial adagium that each case must be decided on its own facts. Although this is a sound legal principle it has, with respect, been used by the courts to find distinctions between cases where none exist in order to arrive at a particular preconceived result. These observations will become apparent in the discussion and analysis of case law in the body of this paper. Thus, the purpose of this paper is to revisit some of the reported judgments on this subject with a view to discussing and, in some cases, critically analyzing the manner in which the courts have applied (or failed to apply) the principles involved in determining the issue at hand. In the course of the paper, some reference (with a brief discussion on occasions) to Australian and English cases will be made with a view both to a comparative study with our law and tapping into the jurisprudence of these two nations in this difficult area of income tax law.